2021
DOI: 10.3201/eid2704.204078
|View full text |Cite
|
Sign up to set email alerts
|

Blastomycosis Surveillance in 5 States, United States, 1987–2018

Abstract: The median time from symptom onset to diagnosis and the severity of illness suggest that surveillance underestimates the true number of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 20 publications
4
29
0
Order By: Relevance
“…Coccidioidomycosis, histoplasmosis, and blastomycosis cases were more common in males, consistent with previous studies (8,14,30), although with substantial differences by pathogen, ranging from 52% of coccidioidomycosis infections to 70% of blastomycosis infections in males. Biologic differences and…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Coccidioidomycosis, histoplasmosis, and blastomycosis cases were more common in males, consistent with previous studies (8,14,30), although with substantial differences by pathogen, ranging from 52% of coccidioidomycosis infections to 70% of blastomycosis infections in males. Biologic differences and…”
Section: Discussionsupporting
confidence: 91%
“…These numbers are substantially lower than those reported in previous studies ( 39 , 40 ), which found that histoplasmosis and blastomycosis result in approximately 5,000 and 1,000 hospitalizations, respectively, each year in the United States according to administrative data, highlighting substantial discrepancies between sources of case reports. Although counts differed considerably, the high hospitalization and mortality rates for histoplasmosis and blastomycosis described in this report align with past surveillance reports ( 8 , 14 , 39 ). In-depth, state-level comparisons of surveillance and administrative hospitalization data are needed to evaluate potential gaps in reporting and accuracy of administrative coding data.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations